Marketing Communication of Trendyol - Veselá, Tereza (2025)
This thesis examines how Trendyol’s influencer-based marketing communication influences brand awareness, brand image, and perceived differentiation in the Czech fast fashion market. The study aimed to determine whether influencer collaborations effectively support Trendyol’s brand-building efforts and how Czech consumers perceive the credibility and authenticity of these partnerships. Combining a theoretical framework with a quantitative survey of Czech consumers revealed that Trendyol’s spontaneous brand awareness is almost nonexistent, while aided awareness remains limited. Respondents associated the brand mainly with affordability and convenience but also with low product quality, which negatively shaped its image. Influencer marketing was identified as the primary source of exposure, yet Trendyol influencers were perceived as less trustworthy and authentic than other Czech creators. Consequently, influencer content increased visibility but had minimal impact on purchase intentions. The findings suggest that Trendyol’s communication strategy requires stronger localisation, clearer communication of product quality, and more credible influencer partnerships to build a differentiated and trustworthy market position.